What light eaudiobook - Asher, Jay (Listening Library, 2016)
THE INSTANT NEW YORK TIMES  BESTSELLER! From Jay Asher, #1 New York Times bestselling author of Thirteen Reasons Why , comes a holiday romance that will break your heart, but soon have you believing in love again. . . .   "A beautiful story of love and forgiveness." —Stephen Chbosky, New York Times bestselling author of The Perks of Being a Wallflower Sierra's family runs a Christmas tree farm in Oregon—it's a bucolic setting for a girl to grow up in, except that every year, they pack up and move to California to set up their Christmas tree lot for the season. So Sierra lives two lives: her life in Oregon and her life at Christmas. And leaving one always means missing the other.  Until this particular Christmas, when Sierra meets Caleb, and one life eclipses the other. By reputation, Caleb is not your perfect guy: years ago, he made an enormous mistake and has been paying for it ever since. But Sierra sees beyond Caleb's past and becomes determined to help him find forgiveness and, maybe, redemption. As disapproval, misconceptions, and suspicions swirl around them, Caleb and Sierra discover the one thing that transcends all else: true love. What Light is a love story that's moving and life-affirming and completely unforgettable.